Geomorphology and global environmental change - Slaymaker, Olav; Spencer, Tom; Embleton Hamann, Christine (Cambridge University Press, 2009)
How will global environmental change affect the landscape and our interaction with it? Apart from climate change, there are other important catalysts of landscape change, including relief, hydroclimate and runoff, sea level variations and human activity. This volume summarizes the state-of-the-art concerning the geomorphic implications of global environmental change, analyzing such effects on lakes, rivers, coasts, reefs, rainforests, savannas, deserts, glacial features, and mountains. Providing a benchmark statement from the worldÕs leading geomorphologists on the current state of, and potential changes to, the environment, this book is invaluable for advanced courses on geomorphology and environmental science, and as a reference for research scientists. Interdisciplinary in scope, with a primary audience of Earth and environmental scientists, geographers, geomorphologists and ecologists, it also has a wider reach to those concerned with the social, economic and political issues raised by global environmental change, and is useful to policy makers and environmental managers.